My Year of Meats - Ozeki, Ruth L. (Edinburgh : Canongate, 2013)
Ruth Ozeki's acclaimed debut novel is 'marvellously funny and passionate' (Jane Smiley) and 'a joy to read' (Elle)
Originally published: New York: Viking; London: Picador, 1998.
ENH
Keywords: Women television producers and directors -- Japan -- Fiction; Television programs -- Japan -- Fiction; Meat industry and trade -- Japan -- Fiction; English literature